2006
DOI: 10.1080/00365510500375230
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and inflammation in pregnancy

Abstract: Pregnancy is a period when increased oxidative stress can be expected. We have focused especially on oxidative stress and inflammation in the period of pregnancy, when prenatal screening is usually performed. We determined advanced oxidation protein products (AOPPs), C-reactive protein (CRP) and anticardiolipin antibodies (ACA) IgG and IgM levels in the serum of 86 pregnant women in the 1st trimester and 102 pregnant women in the 2nd trimester. AOPP levels in the maternal serum of pregnant women were significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 22 publications
1
34
1
1
Order By: Relevance
“…C-reactive protein concentrations are generally higher in pregnant than in nonpregnant women, 37 and placentally derived microparticles or soluble products from the placenta are suspected of driving systemic inflammation during normal pregnancy. 23 An increased inflammatory response during pregnancy is present for preeclampsia, small-for-gestational-age infants, and preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…C-reactive protein concentrations are generally higher in pregnant than in nonpregnant women, 37 and placentally derived microparticles or soluble products from the placenta are suspected of driving systemic inflammation during normal pregnancy. 23 An increased inflammatory response during pregnancy is present for preeclampsia, small-for-gestational-age infants, and preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, during her pregnancy, her CRP levels were increased almost three-fold in subject #II-8, which is similar to the two-to three-fold increase in CRP level observed in normal pregnancy during the second trimester. 27 The CRP level decreased after delivery and was further reduced by statin treatment (Fig. 4).…”
Section: Discussionmentioning
confidence: 90%
“…According to Casanueva & Viteri (2003) these oxidative stresses reached to the peaks by the second trimester of pregnancy and it may cause the death of fetus in the absence of antioxidant. Further, Fialová et al (2006) reported higher level AOPPs (advanced oxidation protein products), CRP (C-reactive protein) and ACA (anticardiolipin antibodies) and IgG in the 1st and 2nd trimesters which reflect a maternal response to inflammatory and oxidative stress in pregnant women. Similarly Toescu et al (2002) reported that last trimester of pregnancy was associated with the formation of susceptible, oxidisable particles (high LDL score) and an increase in oxidative damage and this may increase risk of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 91%